INTEGRATING YOUTUBE STORYTELLING VIDEOS IN A COMMUNICATIVE APPROACH TO TEACHING ENGLISH FOR YOUNG LEARNERS - Wanda Hijriani Herwanto (Universitas Brawijaya, 2022)
This study discusses the application of YouTube which is integrated into the Communicative Language Approach for Young Learner English learning. The ability to communicate is one of the demands in learning a foreign language. An elementary school teacher at an elementary school held a program so that her students could do storytelling. The program applies Youtube Integration to the CLT approach. The main purpose of this research is to focus on investigating how the teacher applies the CLT approach using YouTube and find out its benefits. Qualitative research design was used in this research. The instruments used were observation and semi-structured interviews. data were grouped, analyzed and described. Thus, the findings from this study are teachers using YouTube in the early stages of learning and at the end of the program. The learning steps and objectives are in accordance with the Communicative Approach principles. Furthermore, several benefits were also found such as making learning fun, exposing students, increasing students' pronunciation, vocabulary and confidence in communicating.